2014
DOI: 10.1104/pp.114.236380
|View full text |Cite
|
Sign up to set email alerts
|

Singlet Oxygen Signatures Are Detected Independent of Light or Chloroplasts in Response to Multiple Stresses    

Abstract: The production of singlet oxygen is typically associated with inefficient dissipation of photosynthetic energy or can arise from light reactions as a result of accumulation of chlorophyll precursors as observed in fluorescent (flu)-like mutants. Such photodynamic production of singlet oxygen is thought to be involved in stress signaling and programmed cell death. Here we show that transcriptomes of multiple stresses, whether from light or dark treatments, were correlated with the transcriptome of the flu mutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
81
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(88 citation statements)
references
References 75 publications
6
81
0
1
Order By: Relevance
“…6C). Thus, our analysis here reveals transcriptional footprints that are consistent with previously conducted stress analyses (Hahn et al, 2013) or ROS-inspired meta-analysis (Gadjev et al, 2006;Mor et al, 2014).…”
Section: Ros Transcriptional Footprints Are Found In Environmental Stsupporting
confidence: 88%
See 4 more Smart Citations
“…6C). Thus, our analysis here reveals transcriptional footprints that are consistent with previously conducted stress analyses (Hahn et al, 2013) or ROS-inspired meta-analysis (Gadjev et al, 2006;Mor et al, 2014).…”
Section: Ros Transcriptional Footprints Are Found In Environmental Stsupporting
confidence: 88%
“…6B; Hahn et al, 2013) and supports the 1 O 2 -responsive gene set found in early stress responses ( Fig. 6C; Mor et al, 2014). Footprints associated with specific (subcellular) types of ROS probably exist, although they do not seem to be major discernible factors among diverse studies, except the early 1 O 2 footprint of cluster VI.…”
Section: Timing Of Oxidative Stress Responses As the Determining Factsupporting
confidence: 73%
See 3 more Smart Citations